Pelatihan Penulisan Naskah Lakon pada Komunitas Teater di Kota Mataram: Training in Playwriting for Theater Communities in Mataram City Indonesia - Khairussibyan, Muh.; Jafar, Syamsinas; Intiana, Siti Rohana Hariana; Susanti, Pipit Aprilia (DARMADIKSANI, 2025)
Kesenian teater di NTB khususnya di Mataram kekurangan penulis naskah lakon yang andal. Persoalan minimnya naskah berkualitas tersebut perlu diikhtiarkan solusinya. Salah satu solusinya adalah dengan mengadakan pelatihan penulisan naskah lakon bagi komunitas teater di kota Mataram. Pengabdian berupa pelatihan ini bisa meningkatkan keterampilan para anggota komunitas teater di kota Mataram. Kegiatan pelatihan dilaksanakan dalam tiga tahap yakni tahap penyajian materi teoretis tentang drama realis, struktur drama, tahapan penulisan naskah lakon/drama, teknik pengembangan ide, dan lain-lain. Tahapan kedua adalah pemberian contoh berdasarkan pengalaman pemateri dan naskah yang pernah ditulis pemateri. Tahapan ketiga adalah praktik penentuan ide cerita dan penulisan outline cerita yang akan dikembangkan menjadi naskah lakon. Pada akhir pelatihan disediakan waktu refleksi dan tanya jawab.  The development of theater arts in West Nusa Tenggara (NTB), particularly in Mataram city, is facing a creative drought due to the scarcity of capable play scriptwriters. This absence of strong narrative voices is longing for compelling stories. To solve this, a targeted training program in playwriting was initiated for members of the theater communities in Mataram city. This community service aimed to nurture new talents and sharpen the creative pens of emerging writers. The training was conducted in three phases. The first phase focused on delivering theoretical material, including concepts of realist drama, the structural components of a play, stages of script development, and techniques for generating and refining story ideas. In the second phase, participants were introduced to practical examples drawn from the trainer’s professional experiences and previously written scripts. The third phase involved hands-on practice, where participants were guided in developing story ideas and drafting a structured outline to be expanded into a full play script. The training concluded with a reflection session and a question-and-answer segment, allowing participants to consolidate their learning and clarify any remaining doubts.